2003
DOI: 10.2208/prohe.47.367
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Evaluation of the Mekong River Flood Using Benefit Calculation

Abstract: Flood benefit was calculated for integrated evaluation of the Mekong River flood and inundation in Cambodia. Flood and inundation were simulated using dynamic wave model in main channels and non-uniform flow model for flooded area. Agricultural, industrial and fishery benefits were mainly considered. Data were obtained from field and literature survey. The estimated benefits were about 20 billion-FY for rice production and 10 billion-FY for fish catch in the case of the 2000 flood. On the other hand, the damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In this study, as well, occasional embankment collapse could be one of the possible sources of suspended sediments and phosphorus. In fact, Kazama et al (2003) pointed out serious riverbank erosion and bank retreat along the middle reach of the Mekong River. The contribution of bank failures as one of the sources of sediment and attached nutrients to the river should be further evaluated quantitatively, as Kummu et al (2008) showed that although the bank erosion in the Vientiane–Nong Khai area is locally significant, in global scale the erosion is very low.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, as well, occasional embankment collapse could be one of the possible sources of suspended sediments and phosphorus. In fact, Kazama et al (2003) pointed out serious riverbank erosion and bank retreat along the middle reach of the Mekong River. The contribution of bank failures as one of the sources of sediment and attached nutrients to the river should be further evaluated quantitatively, as Kummu et al (2008) showed that although the bank erosion in the Vientiane–Nong Khai area is locally significant, in global scale the erosion is very low.…”
Section: Discussionmentioning
confidence: 99%
“…And it leads to lower the groundwater levels and decrease the usage of groundwater resources in the downstream region (Koontanakulvong and Suthidhummajit, 1999). This problem impacts not only human activities, but also fisheries and ecosystems because fish production and natural carbonic fertilizers are direct benefits during flooding seasons and these benefits are more valuable than flood damages (Kazama et al, 2003).…”
Section: Effects Controlling the Inundation Areasmentioning
confidence: 99%
“…The Kampong Cham and Prey Veng provinces have agricultural land and require inundation agriculture along the rivers, as shown in Figure 9. The Kampong Chhnang province not only has agriculture but also fishery production which correlates to the water level (Baran et al, 2001;Kazama et al, 2003b) and requires flooding more than other provinces, as fishery production is one of the biggest national industries in Cambodia (Gum, 2000). The Kandal province is located between the Mekong and Bassac Rivers and has a huge flooding area with a higher water level for a long period.…”
Section: Spatial Control Of Floodingmentioning
confidence: 99%
“…Therefore, we were unable to grasp the damage in time series, though this is necessary for efficient flood control on temporal and spatial scales. Kazama et al (2003b) estimated the influence of floods in the economy using a benefit method and flood simulation. However, this research considered only the agriculture and fishery sections and did not consider future development of manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%